Cross-cultural adaptation of the sinus and nasal quality of life survey (SN-5) to Spanish. (December 2020) - Calvo-Henríquez, Christian; Valencia-Blanco, Beatriz; Boronat-Catalá, Borja; Maza-Solano, Juan; Díaz-Anadón, Águeda; Kahn, Sandra; Moure-Gonzalez, Jose D.; Faraldo-García, Ana; Martinez-Capoccioni, Gabriel
Abstract: Objective: There is a high prevalence for rhinitis with an increasing trend. However, there is a lack of specific quality of life pediatric questionnaires for sinonasal symptoms. The Sinus and Nasal Quality of Life Survey (SN-5) is the only validated instrument specifically designed with this objective. In this work we have translated and validated the Spanish version of the SN5 questionnaire. Methods: The SN5 was translated according to the World Health Organization recommendation for the translation and adaptation of instruments. The final version of the Sp-SN5 was administered twice (day 0 and day 7) to 137 participants with and without sinonasal symptoms. Reliability was measured with Cronbach α, temporal stability was measured with intraclass correlation coefficient. External validity was assessed with a ROC curve comparing a cohort of cases (children going to turbinate radiofrequency ablation) and controls (asymptomatic children). Results: A Spearman correlation between the total result of the Sp-SN-5 questionnaire and the QOL score showed a strong negative correlation in the general sample and all the age subgroups. Internal consistency measured with Cronbach α was 0.87 for 5 items and was still over 0.83 after removing each item of the test. The intraclass correlation coefficient (ICC) for test-retest measurements was 0.94. The receiver operating characteristic (ROC) curve for all the included participants showed a very high area under the curve (0.998). Conclusions: The Sp–SN–5 questionnaire was successfully translated and cross-culturally adapted into Spanish, and the translated version exhibited adequate properties. The survey was effective in assessing the quality of life of pediatric patients with sinonasal complaints and can be used for this purpose both in a clinical setting and in future research.